High-strength aluminum alloy material for automobile calipers and production process of high-strength aluminum alloy material
By adding nanosilica, Cu-MOF, graphene nanosheets and titanium boronide powder composite reinforced powder to the aluminum alloy material for automotive calipers, the problem of imbalance in mechanical properties and high temperature resistance of aluminum alloy materials is solved. The obtained materials maintain good mechanical properties under high temperature conditions and reduce deformation risks.
Patent Information
- Application Number
- CN202510119887.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The mechanical properties and high-temperature resistance of aluminum alloy materials for automotive calipers are unbalanced, which may cause deformation under high temperature conditions. In severe cases, the brake disc may be locked and traffic accidents may be caused.
The composite reinforced powder is obtained by compositeing nanosilicon dioxide, Cu-MOF, graphene nanosheets and titanium boronide powder. The refinement effect of graphene on the silicon phase in the aluminum alloy material is used to weaken the influence of high silicon content on the heat resistance of aluminum alloy, and the aluminum phase grains of aluminum alloy material are used to refine the aluminum phase grains of aluminum alloy material to improve the heat resistance of aluminum alloy material.
The aluminum alloy material for automotive calipers produced has good mechanical properties, high strength, excellent high temperature resistance and good thermal conductivity. It can maintain good mechanical properties under high temperature conditions and reduce deformation caused by long-term high temperatures.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy materials, and in particular relates to a high-strength aluminum alloy material for automobile calipers and a production process thereof. Background Art
[0002] Brake calipers are important safety components on cars and play a role in braking. With the development of lightweight cars, high-performance cars pursue extreme lightweight, and the utilization rate of lightweight material aluminum is getting higher and higher. Aluminum alloy brake calipers have occupied a dominant position. Traditional brake calipers are mainly formed by gravity casting of aluminum alloy metal molds, which have problems such as low strength and heavy weight. Low-pressure casting can solve the contradiction between stable filling of molten metal and solidification shrinkage compensation in traditional gravity casting. It has a strong shrinkage compensation function, making the aluminum alloy brake caliper dense in structure, good in mechanical properties and high in strength.
[0003] The patent application with publication number CN117845108A discloses a high-strength and toughness aluminum alloy brake caliper and its extrusion casting method. By preparing aluminum alloy liquid, removing slag and hydrogen, extrusion casting, solid solution and aging treatment, the α-Al grains and eutectic Si phase are refined, the purity of the aluminum alloy liquid is improved, hydrogen pores are eliminated, and the strength and plasticity of the aluminum alloy brake caliper are improved.
[0004] The patent application with publication number CN108048710A discloses an extrusion casting high-strength and toughness aluminum alloy and an extrusion casting method thereof, which refines α-Al grains, modifies Fe-rich phase and eutectic Si phase, and improves the strength and plasticity of the extrusion casting aluminum alloy through smelting aluminum alloy liquid, refining, degassing and slag removal, extrusion casting and solid solution aging treatment.
[0005] The above two solutions improve the mechanical properties and wear resistance of aluminum alloy by adding silicon to it. However, the addition of a large amount of silicon will lead to a decrease in the thermal conductivity of aluminum alloy. The calipers of automobiles will generate a high temperature of 150-300°C in emergency braking and long downhill braking. The high temperature will cause the aluminum alloy calipers to deform, which may seriously cause the brake disc to lock, causing the vehicle to lose control and causing serious traffic accidents. Therefore, it is also necessary to make the aluminum alloy material used for the caliper have high temperature resistance and good thermal conductivity, so as to reduce the deformation of the caliper caused by long-term high temperature. Summary of the invention
[0006] The purpose of the present invention is to solve the problem of unbalanced mechanical properties and high temperature resistance of aluminum alloy for automobile calipers, and to provide a high-strength aluminum alloy material for automobile calipers and a production process thereof.
[0007] The present invention prepares composite strengthening powder by compounding nano silicon dioxide, Cu-MOF, graphene nanosheets and titanium boride powder, utilizes the refining effect of graphene on the silicon phase in the aluminum alloy material to weaken the influence of high silicon content on the heat resistance of the aluminum alloy, utilizes titanium boride powder to refine the aluminum phase grains of the aluminum alloy material and improve the heat resistance of the aluminum alloy material, and obtains aluminum alloy material for automobile calipers with excellent mechanical properties and high temperature resistance.
[0008] The purpose of the present invention can be achieved through the following technical solutions: A high-strength aluminum alloy material for automobile calipers, comprising the following components by mass percentage: Si 10.36-11.58%, Fe 1.23-2.14%, Cu 1.05-1.17%, RE 0.32-0.35%, Sr 0.18-0.21%, composite strengthening powder 3.55-3.85%, the balance is pure aluminum; Si, Fe and Cu are mixed with pure aluminum in the form of master alloys Al-20Si alloy, Al-20Fe alloy and Al-50Cu alloy, respectively; RE and Sr are mixed with pure aluminum in the form of modified alloys Al-10RE alloy and Al-10Sr alloy, respectively; RE is a mixture of rare earth elements La and Ce.
[0009] Furthermore, the composite reinforced powder is prepared by the following steps: In a reactor, Cu-MOF / graphene nanosheets and 1-ethyl-3-methylimidazole bromide are ultrasonically dispersed in deionized water, modified silica is added to the reactor, and after ultrasonic dispersion, the temperature is raised to 90-100° C. and stirred until the solution evaporates, and then the precipitate is placed in a tubular furnace and calcined at 250-280° C. for 20-30 min under nitrogen protection to obtain a composite reinforced powder.
[0010] Furthermore, the usage ratio of Cu-MOF / graphene nanosheets, 1-ethyl-3-methylimidazole bromide, deionized water and modified silica is 2-4 g: 1.2-1.5 g: 100-200 mL: 4-5 g.
[0011] Further, Cu-MOF / graphene nanosheets are prepared by the following steps: In a reaction kettle, titanium boride powder is ultrasonically dispersed in a primary ethanol solvent, and then thioglycolic acid is added, and the mixture is modified by shaking for 20-24 hours. The precipitate is collected by centrifugation, washed with ethanol, and then dispersed in a secondary ethanol solvent in a reaction kettle again. Copper hydroxide graphene nanosheets are added and ultrasonically dispersed. Then, terephthalic acid is dissolved in a 70wt% ethanol solution and added to the reaction kettle. The mixture is heated to 100-120°C and reacted in a closed manner for 12-16 hours. After filtering, the precipitate is washed with ethanol and deionized water, and vacuum dried at 60-70°C to obtain Cu-MOF / graphene nanosheets. Both the primary ethanol solvent and the secondary ethanol solvent are anhydrous ethanol.
[0012] Furthermore, the dosage ratio of titanium boride powder, primary ethanol solvent, thioglycolic acid, secondary ethanol solvent, copper hydroxide graphene nanosheets, terephthalic acid and 70wt% ethanol solution is 3-4g:100-200mL:10-12mL:100-200mL:4-5g:8-10g:150-200mL.
[0013] Further, the copper hydroxide graphene nanosheets are prepared by the following steps: Copper nitrate trihydrate and graphene nanosheets are dispersed in ethanol in a reaction kettle, and a 2M sodium hydroxide ethanol solution is added dropwise into the reaction kettle under magnetic stirring. After stirring for 1-2 hours, the mixture is filtered off and the precipitate is washed with deionized water and vacuum dried at 60-70° C. for 10-12 hours to obtain copper hydroxide graphene nanosheets.
[0014] Furthermore, the usage ratio of copper nitrate trihydrate, graphene nanosheets, ethanol and sodium hydroxide ethanol solution is 4-5g:2-3g:50-80mL:30-40mL.
[0015] Further, the modified silica is prepared by the following steps: The nano-silica microspheres are immersed in a 1M hydrochloric acid solution for activation for 2-3 hours, and then centrifuged to separate the precipitate. The precipitate is washed with deionized water, and then ultrasonically dispersed in a 0.1wt% sodium dodecylbenzene sulfonate aqueous solution and stirred for 4-5 hours for modification. After centrifugation, the precipitate is washed with deionized water and vacuum dried at 70-80°C for 10-12 hours to obtain modified silica.
[0016] A production process of high-strength aluminum alloy material for automobile calipers, comprising the following steps: Put pure aluminum and intermediate alloy into a drying oven at 180-200°C and dry for 30-40 minutes, melt pure aluminum at 720-740°C in a resistance furnace, add intermediate alloy and composite strengthening powder, stir for 2-5 minutes, keep warm for 20-30 minutes, then add modified alloy, stir for 2-5 minutes, keep warm for 10-20 minutes, cool to 680-720°C, mix refining agent and slag remover, add into resistance furnace to remove slag for 2-5 minutes, let stand for 5-8 minutes after slag removal, pour into metal mold, and obtain high-strength aluminum alloy material for automobile calipers after artificial aging treatment.
[0017] Furthermore, the addition amount of the refining agent and the slag remover is 0.5-0.6% of the total mass of the aluminum alloy, the refining agent model is YT-J-1, and the slag remover model is YT-D-4.
[0018] Beneficial effects of the present invention: The high-strength aluminum alloy material for automobile calipers prepared by the present invention has good mechanical properties and high strength, and also has excellent high-temperature resistance and good thermal conductivity. Composite strengthening powder is added to the formula of the aluminum alloy material, titanium boride in the composite strengthening powder is used to refine the grains of the aluminum alloy material, and graphene nanosheets are used to refine the silicon phase grains in the aluminum alloy material, so as to reduce the influence of high silicon content on the aluminum alloy material and improve the mechanical strength and high-temperature resistance of the aluminum alloy material.
[0019] The high-strength aluminum alloy material for automobile calipers prepared by the production process of the present invention has small grains and high mechanical strength. Cu-MOF is synthesized on the surface of graphene nanosheets, copper and aluminum bonding is used to promote the dispersion of the graphene nanosheets, and Cu-MOF is used to combine the graphene nanosheets with titanium boride powder, thereby further improving the dispersibility of titanium boride. Finally, nano silicon dioxide is bonded to the Cu-MOF / graphene nanosheets, thereby reducing the amount of aluminum alloy slag generated and improving the physical properties of the aluminum alloy material. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Embodiment 1: A high-strength aluminum alloy material for automobile calipers, comprising the following components by mass percentage: Si 10.36%, Fe 1.23%, Cu 1.05%, RE 0.32%, Sr 0.18%, composite strengthening powder 3.55%, and the balance is pure aluminum.
[0022] Si, Fe and Cu are mixed with pure aluminum in the form of master alloys Al-20Si alloy, Al-20Fe alloy and Al-50Cu alloy, respectively.
[0023] RE and Sr are mixed with pure aluminum in the form of modified alloys Al-10RE alloy and Al-10Sr alloy, respectively.
[0024] RE is a mixture of rare earth elements La and Ce.
[0025] A production process of high-strength aluminum alloy material for automobile calipers, comprising the following steps: S1. Disperse 4 g of copper nitrate trihydrate and 2 g of graphene nanosheets in 50 mL of ethanol in a reactor. Add 30 mL of 2 M sodium hydroxide ethanol solution dropwise into the reactor under magnetic stirring. Stir the reaction for 1 h and then filter. Wash the precipitate with deionized water and vacuum dry it at 60 °C for 10 h to obtain copper hydroxide graphene nanosheets.
[0026] S2. In a reactor, ultrasonically disperse 3 g of titanium boride powder in 100 mL of anhydrous ethanol, add 10 mL of thioglycolic acid, shake and modify for 20 h, collect the precipitate by centrifugation, wash with ethanol, and disperse it again in 100 mL of anhydrous ethanol in a reactor, add 4 g of copper hydroxide graphene nanosheets and ultrasonically disperse them, then dissolve 8 g of terephthalic acid in 150 mL of 70 wt% ethanol solution and add it to the reactor, heat to 100 ° C and react in a closed state for 12 h, filter and wash the precipitate with ethanol and deionized water, and vacuum dry at 60 ° C to obtain Cu-MOF / graphene nanosheets.
[0027] S3. Soak the nano-silica microspheres in a 1M hydrochloric acid solution for activation for 2 hours, then centrifuge to separate the precipitate, wash the precipitate with deionized water, ultrasonically disperse the precipitate in a 0.1wt% sodium dodecylbenzene sulfonate aqueous solution, and stir for 4 hours for modification. After centrifugation, wash the precipitate with deionized water, and vacuum dry at 70°C for 10 hours to obtain modified silica.
[0028] S4. Ultrasonic dispersion of 2 g Cu-MOF / graphene nanosheets and 1.2 g 1-ethyl-3-methylimidazole bromide in 100 mL deionized water was performed in a reactor. 4 g modified silica was added to the reactor. After ultrasonic dispersion, the temperature was raised to 90° C. and stirred until the solution evaporated. The precipitate was placed in a tubular furnace and calcined at 250° C. for 20 min under nitrogen protection to obtain a composite reinforced powder.
[0029] S5. Put pure aluminum and intermediate alloy into a drying oven at 180°C and dry for 30 minutes. Melt pure aluminum at 720°C in a resistance furnace, add intermediate alloy and composite strengthening powder, stir for 2 minutes, keep warm for 20 minutes, then add modified alloy, stir for 2 minutes and keep warm for 10 minutes. After cooling to 680°C, mix refining agent and slag remover and add them into a resistance furnace to remove slag for 25 minutes. After slag removal, let it stand for 5 minutes, pour it in a metal mold, and obtain high-strength aluminum alloy material for automobile calipers after artificial aging treatment.
[0030] The refining agent model is YT-J-1, the slag remover model is YT-D-4, and the addition amount of the refining agent and the slag remover is 0.5% of the total mass of the aluminum alloy.
[0031] Embodiment 2: A high-strength aluminum alloy material for automobile calipers, comprising the following components by mass percentage: Si 11.02%, Fe 1.78%, Cu 1.11%, RE 0.34%, Sr 0.19%, composite strengthening powder 3.65%, and the balance is pure aluminum.
[0032] Si, Fe and Cu are mixed with pure aluminum in the form of master alloys Al-20Si alloy, Al-20Fe alloy and Al-50Cu alloy, respectively.
[0033] RE and Sr are mixed with pure aluminum in the form of modified alloys Al-10RE alloy and Al-10Sr alloy, respectively.
[0034] RE is a mixture of rare earth elements La and Ce.
[0035] A production process of high-strength aluminum alloy material for automobile calipers, comprising the following steps: S1. Disperse 4.5 g of copper nitrate trihydrate and 2.5 g of graphene nanosheets in 65 mL of ethanol in a reactor. Add 35 mL of 2 M sodium hydroxide ethanol solution dropwise into the reactor under magnetic stirring. Stir the reaction for 1.5 h and then filter. Wash the precipitate with deionized water and vacuum dry it at 65 °C for 11 h to obtain copper hydroxide graphene nanosheets.
[0036] S2. In a reactor, ultrasonically disperse 3.5 g of titanium boride powder in 150 mL of anhydrous ethanol, add 11 mL of thioglycolic acid, shake for 22 h, collect the precipitate by centrifugation, wash with ethanol, and disperse it again in 150 mL of anhydrous ethanol in a reactor, add 4.5 g of copper hydroxide graphene nanosheets and ultrasonically disperse them, then dissolve 9 g of terephthalic acid in 175 mL of 70 wt% ethanol solution and add it to the reactor, heat to 110 ° C and seal the reaction for 14 h, filter and wash the precipitate with ethanol and deionized water, and dry it in vacuo at 65 ° C to obtain Cu-MOF / graphene nanosheets.
[0037] S3. Soak the nano-silica microspheres in a 1M hydrochloric acid solution for activation for 2.5 hours, then centrifuge to separate the precipitate, wash the precipitate with deionized water, ultrasonically disperse the precipitate in a 0.1wt% sodium dodecylbenzene sulfonate aqueous solution, and stir for 4.5 hours for modification. After centrifugation, wash the precipitate with deionized water, and vacuum dry at 75°C for 11 hours to obtain modified silica.
[0038] S4. Ultrasonic dispersion of 3 g Cu-MOF / graphene nanosheets and 1.35 g 1-ethyl-3-methylimidazole bromide in 150 mL deionized water was performed in a reactor. 4.5 g modified silica was added to the reactor. After ultrasonic dispersion, the temperature was raised to 95° C. and stirred until the solution evaporated. The precipitate was placed in a tubular furnace and calcined at 265° C. for 25 min under nitrogen protection to obtain a composite reinforced powder.
[0039] S5. Put pure aluminum and intermediate alloy into a drying oven at 190°C and dry for 35 minutes. Melt pure aluminum at 730°C in a resistance furnace, add intermediate alloy and composite strengthening powder, stir for 3 minutes, keep warm for 25 minutes, then add modified alloy, stir for 3 minutes and keep warm for 15 minutes. After cooling to 700°C, mix refining agent and slag remover and add them into a resistance furnace to remove slag for 3 minutes. After slag removal, let it stand for 6 minutes, pour it in a metal mold, and obtain high-strength aluminum alloy material for automobile calipers after artificial aging treatment.
[0040] The refining agent model is YT-J-1, the slag remover model is YT-D-4, and the addition amount of the refining agent and the slag remover is 0.55% of the total mass of the aluminum alloy.
[0041] Embodiment 3: A high-strength aluminum alloy material for automobile calipers, comprising the following components by mass percentage: Si 11.58%, Fe 2.14%, Cu 1.17%, RE 0.35%, Sr 0.21%, composite strengthening powder 3.85%, and the balance is pure aluminum.
[0042] Si, Fe and Cu are mixed with pure aluminum in the form of master alloys Al-20Si alloy, Al-20Fe alloy and Al-50Cu alloy, respectively.
[0043] RE and Sr are mixed with pure aluminum in the form of modified alloys Al-10RE alloy and Al-10Sr alloy, respectively.
[0044] RE is a mixture of rare earth elements La and Ce.
[0045] A production process of high-strength aluminum alloy material for automobile calipers, comprising the following steps: S1. Disperse 5 g of copper nitrate trihydrate and 3 g of graphene nanosheets in 80 mL of ethanol in a reactor. Add 40 mL of 2 M sodium hydroxide ethanol solution dropwise into the reactor under magnetic stirring. Stir the reaction for 2 h and then filter. Wash the precipitate with deionized water and vacuum dry at 70 °C for 12 h to obtain copper hydroxide graphene nanosheets.
[0046] By in-situ synthesizing graphene nanosheets coated with copper hydroxide particles, the surface of the graphene nanosheets is coated with copper elements, thereby reducing the upward floating of the graphene nanosheets in the molten aluminum alloy during the preparation of the aluminum alloy, while ensuring the integrity of the graphene nanosheets. The bonding of aluminum and copper promotes the compatibility of the graphene nanosheets with the aluminum alloy, improves the dispersibility of the graphene nanosheets in the aluminum alloy, and utilizes the refinement effect of graphene on the silicon phase to improve the strength and temperature resistance of the aluminum alloy.
[0047] S2. In a reactor, 4 g of titanium boride powder was ultrasonically dispersed in 200 mL of anhydrous ethanol, and then 12 mL of thioglycolic acid was added. The mixture was modified by shaking for 24 h, and the precipitate was collected by centrifugation. After washing with ethanol, the precipitate was dispersed in 200 mL of anhydrous ethanol in a reactor again. 5 g of copper hydroxide graphene nanosheets were added and ultrasonically dispersed. Then 10 g of terephthalic acid was dissolved in 200 mL of 70 wt% ethanol solution and added to the reactor. The temperature was raised to 120 ° C and the reaction was closed for 16 h. After filtering, the precipitate was washed with ethanol and deionized water, and vacuum dried at 70 ° C to obtain Cu-MOF / graphene nanosheets.
[0048] The surface of titanium boride powder is modified by thioglycolic acid, so that graphene nanosheets containing copper hydroxide on the surface are grafted on the surface of titanium boride powder during ultrasonic dispersion. After heating reaction, Cu-MOF is generated in situ with terephthalic acid at the position of copper hydroxide, so that the graphene nanosheets cover the surface of titanium boride powder, thereby improving the compatibility of titanium boride powder in aluminum alloy. Titanium boride is thermodynamically stable, has good wettability in aluminum alloy, and has the effect of refining grains, thereby improving the strength and heat resistance of aluminum alloy.
[0049] S3. Soak the nano-silica microspheres in a 1M hydrochloric acid solution for activation for 3 hours, then centrifuge to separate the precipitate, wash the precipitate with deionized water, ultrasonically disperse the precipitate in a 0.1wt% sodium dodecylbenzene sulfonate aqueous solution, and stir for 5 hours for modification. After centrifugation, wash the precipitate with deionized water, and vacuum dry at 80°C for 12 hours to obtain modified silica.
[0050] S4. Ultrasonic disperse 4 g of Cu-MOF / graphene nanosheets and 1.5 g of 1-ethyl-3-methylimidazole bromide in 200 mL of deionized water in a reactor, add 5 g of modified silica to the reactor, raise the temperature to 100 ° C and stir until the solution evaporates after ultrasonic dispersion, then place the precipitate in a tubular furnace and calcine at 280 ° C for 30 min under nitrogen protection to obtain a composite reinforced powder.
[0051] Modified silica is bonded to Cu-MOF / graphene nanosheets using 1-ethyl-3-methylimidazole as an adhesive. After solvent evaporation and calcination, 1-ethyl-3-methylimidazole will solidify and solidify, so that silica is evenly bonded to the Cu-MOF on the surface of the Cu-MOF / graphene nanosheets. Nano-silica can reduce the amount of aluminum alloy slag produced and reduce metal loss caused by oxidation. It can also be used as a magnesium remover to remove magnesium from aluminum alloys and improve the physical properties of aluminum alloy materials.
[0052] S5. Put pure aluminum and intermediate alloy into a drying oven at 200°C and dry for 40 minutes. Melt pure aluminum at 740°C in a resistance furnace, add intermediate alloy and composite strengthening powder, stir for 5 minutes, keep warm for 30 minutes, then add modified alloy, stir for 5 minutes and keep warm for 20 minutes. After cooling to 720°C, mix refining agent and slag remover and add them into a resistance furnace to remove slag for 5 minutes. After slag removal, let it stand for 8 minutes, pour it in a metal mold, and obtain high-strength aluminum alloy material for automobile calipers after artificial aging treatment.
[0053] The refining agent model is YT-J-1, the slag remover model is YT-D-4, and the addition amount of the refining agent and the slag remover is 0.6% of the total mass of the aluminum alloy.
[0054] Comparative Example 1: The difference from Example 1 is that 4 g of copper nitrate hexahydrate is dispersed in 8 g of terephthalic acid ethanol solution in a reactor, heated to 120° C. and reacted in a closed state for 12 h. After filtering, the precipitate is washed with ethanol and deionized water, and vacuum dried at 60° C. to obtain Cu-MOF.
[0055] In a reactor, 2 g of Cu-MOF and 1.2 g of 1-ethyl-3-methylimidazole bromide were ultrasonically dispersed in 100 mL of deionized water, and 4 g of modified silica was added to the reactor. After ultrasonic dispersion, the temperature was raised to 90 ° C and stirred until the solution evaporated. The precipitate was then placed in a tubular furnace and calcined at 250 ° C for 20 min under nitrogen protection to obtain Cu-MOF / nanosilica powder.
[0056] In S5, graphene nanosheets, titanium boride powder and Cu-MOF / nano-silicon dioxide powder are mechanically mixed and then replaced with composite strengthening powder to obtain high-strength aluminum alloy material for automobile calipers.
[0057] Comparative Example 2: The difference from Example 1 is that, S2, 4 g of copper hydroxide graphene nanosheets are ultrasonically dispersed in a reactor, and then 8 g of terephthalic acid is dissolved in 150 mL of 70 wt% ethanol solution and added to the reactor, the temperature is raised to 100 ° C and the reaction is closed for 12 hours, and the precipitate is washed with ethanol and deionized water after filtering, and vacuum dried at 60 ° C to obtain MOF / graphene nanosheets, and the MOF / graphene nanosheets and 3 g of titanium boride powder are used to replace the Cu-MOF / graphene nanosheets to obtain a high-strength aluminum alloy material for automotive calipers.
[0058] Comparative Example 3: The difference from Example 1 is that the composite strengthening powder is replaced by Cu-MOF / graphene nanosheets to prepare a high-strength aluminum alloy material for automobile calipers.
[0059] The performance of the samples made of high-strength aluminum alloy material for the automobile calipers prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested. The hardness of the aluminum alloy samples was tested according to standard GB / T 231.1. The test load was 62.5 kg, the steel ball diameter was 2.5 mm, and after the steel ball was pressed into the sample, the holding time was 60 s.
[0060] According to the standard GB / T 34220-2017 "Test method for high temperature tensile strength of refractory materials", the tensile strength of aluminum alloy samples at 300℃ and 350℃ was tested; According to the standard JJF 1298-2011 "High-temperature creep and rupture strength testing machine type evaluation outline", the creep stress index of aluminum alloy samples was tested at 350°C and 40Mpa. The results are shown in Table 1: Table 1 Performance test table of samples made of high-strength aluminum alloy materials for automobile calipers
[0061] It can be seen from Table 1 that the high-strength aluminum alloy material for automobile calipers prepared in Examples 1 to 3 of the present invention has excellent mechanical properties and high temperature resistance, and can still maintain good mechanical properties at high temperatures. After fatigue cycles, compared with Comparative Examples 1 to 3, it has higher tensile strength and good fatigue resistance.
[0062] In Comparative Example 1, since the graphene nanosheets were not modified with copper, the graphene nanosheets and titanium boride had poor compatibility in the aluminum alloy matrix, and the performance of the obtained aluminum alloy material was poor.
[0063] In Comparative Example 2, since the copper hydroxide graphene nanosheets and the titanium boride powder are not compounded, the dispersion of the titanium boride powder in the aluminum alloy matrix is low, and the high temperature resistance of the aluminum alloy material is slightly improved.
[0064] In Comparative Example 3, since nano-silicon dioxide and Cu-MOF / graphene nanosheets were not combined to produce a composite reinforced powder, when Cu-MOF was smelted with the aluminum alloy material matrix, the ligand carbonization produced impurities, which increased the amount of slag produced, increased the amount of metal loss, and reduced the physical properties of the aluminum alloy material.
[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-strength aluminum alloy material for automobile calipers, characterized in that: Calculated by weight percentage, it contains the following components: Si 10.36-11.58%, Fe 1.23-2.14%, Cu 1.05-1.17%, RE 0.32-0.35%, Sr 0.18-0.21%, composite strengthening powder 3.55-3.85%, the balance is pure aluminum; The composite reinforced powder is prepared by the following steps: In a reaction kettle, Cu-MOF / graphene nanosheets and 1-ethyl-3-methylimidazole bromide are ultrasonically dispersed in deionized water, modified silica is added to the reaction kettle, and after ultrasonic dispersion, the temperature is raised to 90-100° C. and stirred until the solution evaporates, and then the precipitate is placed in a tubular furnace and calcined at 250-280° C. for 20-30 minutes under nitrogen protection to obtain a composite reinforced powder; The Si, Fe and Cu are mixed with pure aluminum in the form of master alloys Al-20Si alloy, Al-20Fe alloy and Al-50Cu alloy respectively; The RE and Sr are mixed with pure aluminum in the form of modified alloys Al-10RE alloy and Al-10Sr alloy respectively; The RE is a mixture of rare earth elements La and Ce.
2. The high-strength aluminum alloy material for automobile calipers according to claim 1, characterized in that: The usage ratio of the Cu-MOF / graphene nanosheets, 1-ethyl-3-methylimidazole bromide, deionized water and modified silicon dioxide is 2-4 g: 1.2-1.5g: 100-200mL: 4-5g.
3. The high-strength aluminum alloy material for automobile calipers according to claim 1, characterized in that: The Cu-MOF / graphene nanosheets are prepared by the following steps: In a reaction kettle, titanium boride powder is ultrasonically dispersed in a primary ethanol solvent, and then thioglycolic acid is added, and the mixture is modified by shaking for 20-24 hours. The precipitate is collected by centrifugation, washed with ethanol, and then dispersed in a secondary ethanol solvent in a reaction kettle again. Copper hydroxide graphene nanosheets are added and ultrasonically dispersed. Then, terephthalic acid is dissolved in a 70wt% ethanol solution and added to the reaction kettle. The mixture is heated to 100-120°C and reacted in a closed manner for 12-16 hours. The precipitate is washed after filtering and vacuum dried to obtain Cu-MOF / graphene nanosheets.
4. The high-strength aluminum alloy material for automobile calipers according to claim 3, characterized in that: The dosage ratio of the titanium boride powder, the primary ethanol solvent, thioglycolic acid, the secondary ethanol solvent, the copper hydroxide graphene nanosheets, terephthalic acid and the 70wt% ethanol solution is 3-4g:100-200mL:10-12mL:100-200mL:4-5g:8-10g:150-200mL; the primary ethanol solvent and the secondary ethanol solvent are both anhydrous ethanol.
5. The high-strength aluminum alloy material for automobile calipers according to claim 3, characterized in that: The copper hydroxide graphene nanosheets are prepared by the following steps: Copper nitrate trihydrate and graphene nanosheets are dispersed in ethanol in a reaction kettle, and a 2M sodium hydroxide ethanol solution is added dropwise into the reaction kettle under magnetic stirring. After stirring for 1-2 hours, the mixture is filtered off and the precipitate is washed with deionized water and vacuum dried at 60-70° C. for 10-12 hours to obtain copper hydroxide graphene nanosheets.
6. The high-strength aluminum alloy material for automobile calipers according to claim 5, characterized in that: The usage ratio of the copper nitrate trihydrate, the graphene nanosheets, the ethanol and the sodium hydroxide ethanol solution is 4-5g:2-3g:50-80mL:30-40mL.
7. The high-strength aluminum alloy material for automobile calipers according to claim 1, characterized in that: The modified silicon dioxide is prepared by the following steps: The nano-silica microspheres are immersed in a 1M hydrochloric acid solution for activation and then centrifuged to separate the precipitate. The precipitate is washed with deionized water and then ultrasonically dispersed in a 0.1wt% sodium dodecylbenzene sulfonate aqueous solution and stirred for modification. The precipitate is washed with deionized water after centrifugation and vacuum dried to obtain modified silica.
8. The production process of a high-strength aluminum alloy material for automobile calipers according to claim 1, characterized in that: The steps include: Put pure aluminum and intermediate alloy into a drying oven at 180-200°C and dry for 30-40 minutes, melt pure aluminum at 720-740°C in a resistance furnace, add intermediate alloy and composite strengthening powder, stir for 2-5 minutes, keep warm for 20-30 minutes, then add modified alloy, stir for 2-5 minutes, keep warm for 10-20 minutes, cool to 680-720°C, mix refining agent and slag remover, add into resistance furnace to remove slag for 2-5 minutes, let stand for 5-8 minutes after slag removal, pour into metal mold, and obtain high-strength aluminum alloy material for automobile calipers after artificial aging treatment.
9. The production process of a high-strength aluminum alloy material for automobile calipers according to claim 8, characterized in that: The addition amount of the refining agent and the slag removal agent is 0.5-0.6% of the total mass of the aluminum alloy. The refining agent model is YT-J-1, and the slag removal agent model is YT-D-4.
Citation Information
Patent Citations
Extrusion casting aluminum alloy with high strength and ductility and extrusion casting method thereof
CN108048710A
High-toughness aluminum alloy brake caliper and extrusion casting method thereof
CN117845108A
Heat-resistant high-strength automobile hub aluminum alloy material
CN114855035A
Coating containing liquid metal and preparation method and application thereof
CN115613027A
Graphene TPV particle and preparation method thereof
CN117700978A